Blanquidades chilenas: elementos para un debate (2023)
For starters, we address the place of whiteness in ideological constructs of Chilean miscegenation. Secondly, we explore whiteness as a category of racial classification in the central region of the country. Finally, we propose some paths of inquiry that allow an in- depth study of Chilean whitenesses, in a dialogue with Anglo-Saxon whiteness studies and the debates on whiteness in Latin America. This article concludes with a brief comment on whiteness in social research in Chile.